Determinants of promotional effectiveness of Kiara College / Salinah Yain - Yain, Salinah (2015)
KIARA College is a newly established higher educational institution in Sabah, Malaysia. As a newly established college, KIARA has to compete with other higher educations that already well-known and has a quite strong brand name. One way for KIARA College to compete with others is through the promotion strategies. Therefore, in this study, the researcher focused on the promotion strategies implemented by KIARA College. This research also studied deeper on the factors that influence the promotional effectiveness of KIARA College. To be specific, this study aims to investigate the relationship between factor influencing the promotional effectiveness of Kiara College - (Advertising; Public Relation; and Internal Promotion) and the promotional effectiveness of Kiara College. The determinant factors were used to identify the most influential promotion strategy towards the promotional effectiveness of Kiara College. Structured questionnaire was used as the method for collecting the data analysis. Sampling sizes of 200 respondents were picked randomly using the simple random sampling to take part on the survey. The finding reveals that public relation and internal promotion were the most significance value which is 0.000. It indicates that the determinants of the two independent variables play the main role on influence the promotional effectiveness of Kiara College. The result of the study shown hypothesis 2 and 3 (H2 and H3 ) are accepted and hypothesis "fil-L) is rejected.